Human TRPA1 is a heat sensor displaying intrinsic U-shaped thermosensitivity - Moparthi, Lavanya; Kichko, Tetyana; Eberhardt, Mirjam; Hogestatt, Edward D.; Kjellbom, Per; Johanson, Urban; Reeh, Peter; Leffler, Andreas; Filipovic, Milos; Zygmunt, Peter M. (Scientific Reports, 2016)
Thermosensitive Transient Receptor Potential (TRP) channels are believed to respond to either cold or heat. In the case of TRP subtype A1 (TRPA1), there seems to be a species-dependent divergence in temperature sensation as non-mammalian TRPA1 is heat-sensitive whereas mammalian TRPA1 is sensitive to cold. It has been speculated but never experimentally proven that TRPA1 and other temperature-sensitive ion channels have the inherent capability of responding to both cold and heat. Here we show that redox modification and ligands affect human TRPA1 (hTRPA1) cold and heat sensing properties in lipid bilayer and whole-cell patch-clamp recordings as well as heat-evoked TRPA1-dependent calcitonin gene-related peptide (CGRP) release from mouse trachea. Studies of purified hTRPA1 intrinsic tryptophan fluorescence, in the absence of lipid bilayer, consolidate hTRPA1 as an intrinsic bidirectional thermosensor that is modified by the redox state and ligands. Thus, the heat sensing property of TRPA1 is conserved in mammalians, in which TRPA1 may contribute to sensing warmth and uncomfortable heat in addition to noxious cold.
EVALuna2:32809